Is Administration of Trastuzumab an Independent Risk Factor for Developing Osteonecrosis of the Jaw Among Metastatic Breast Cancer Patients Under Zoledronic Acid Treatment?. Issue 18 (May 2015) - Pilanci, Kezban Nur; Alco, Gul; Ordu, Cetin; Sarsenov, Dauren; Celebi, Filiz; Erdogan, Zeynep; Agacayak, Filiz; Ilgun, Serkan; Tecimer, Coskun; Demir, Gokhan; Eralp, Yesim; Okkan, Sait; et al.
<x xml:space="preserve">Abstract</x> Abstract One of the most important adverse effects of zoledronic acid (ZA) is osteonecrosis of the jaw (ONJ). In previous literature, several risk factors have been identified in the development of ONJ. In this study, we aimed to determine the role of trastuzumab, an antiangiogenic agent, as an independent risk factor for the development of this serious side effect. Our study included 97 patients (mean age: 54 ± 10 years) with breast cancer, recorded in the archives of the Istanbul Florence Nightingale Breast Study Group, who received ZA therapy due to bone metastases between March 2006 and December 2013. We recorded the patients' ages, weights, duration of treatment with ZA, number of ZA infusions, dental procedures, anticancer treatments (chemotherapy, aromatase inhibitor, trastuzumab), the presence of diabetes mellitus or renal dysfunction, and smoking habits. Thirteen patients (13.40%) had developed ONJ. Among the patients with ONJ, the mean time of exposure to ZA was 41 months (range: 13–82) and the mean number of ZA infusions was 38 (range: 15–56). The duration of treatment with ZA and the use of trastuzumab were observed to be 2 factors that influenced the development of ONJ (P = 0.049 and P = 0.028, respectively). The development of ONJ under ZA treatment may be associated solely with the duration of ZA treatment and the concurrent administration of trastuzumab. These findings show that patients who are administered trastuzumab for metastatic breast cancer while undergoing ZA treatment are prone to developing ONJ. Therefore, we recommend intense clinical observation to avoid this particular condition in patients receiving ZA and trastuzumab.